2016
DOI: 10.1002/pc.24013
|View full text |Cite
|
Sign up to set email alerts
|

Structures and high fluorescence of novel nanocomposites of sodium carboxymethyl cellulose/Tb(III) prepared at different pHs

Abstract: Lanthanide metal complexes as novel luminescent metal‐organic frameworks with potential application such as probes, sensors and labels, have greatly been developed. This paper presents novel nanocomposites by reacting terbium salt with the sodium carboxymethyl cellulose (NaCMC) at different pHs, Which were characterized by SEM, TEM, FTIR, XPS, WAXD, GPC, UV‐Vis, and PL. The results show that Tb3+ ions react with O of COO‐, ‐OH, and ‐COC on NaCMC. The morphologies of these nanocomposites showed spheroidal‐like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…These composites suspensions exhibit homogeneous good stability, and there were no visible changes of these suspensions for a month. By our previous reports, the sizes of the composites are in nanoscale. The nanoscale composites in these suspensions could result in a uniform dispersion of the composites and a good stability of suspensions . From the insets in Figure it is observed that suspensions of CE, CT, HE, HT retain the shear-thinning properties of CMC and HPCMC.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…These composites suspensions exhibit homogeneous good stability, and there were no visible changes of these suspensions for a month. By our previous reports, the sizes of the composites are in nanoscale. The nanoscale composites in these suspensions could result in a uniform dispersion of the composites and a good stability of suspensions . From the insets in Figure it is observed that suspensions of CE, CT, HE, HT retain the shear-thinning properties of CMC and HPCMC.…”
Section: Resultsmentioning
confidence: 73%
“…Cellulosic derivatives, especially carboxymethyl cellulose (CMC) and hydroxypropyl carboxymethyl cellulose (HPCMC) (their structures diagram shown in Figure ), have been used in the process of paper coating in the paper-making industry because they can improve the water retention and rheological properties of coatings . Our team has demonstrated that CMC could be used as the sensitizing ligand, and the rare earth­(RE)/CMC nanocomposites have excellent fluorescent properties. The trivalent rare earth­(RE) ions can show abundant emission colors based on their f–f transitions after the absorption of energy. They have many applications in many fields such as modern lighting and display. But the luminescence of RE ions originates from the intra-4f transitions, which are forbidden in principle, resulting in irrelatively low emission efficiency. , An effective approach to increase the luminescent efficiency is to coordinate RE ions with other sensitive ligands, such as cellulose and its derivatives as efficient ligands. The RE/sensitizing ligand systems possess many advantages such as long emission lifetimes, high quantum efficiency narrow bandwidths, high color purities, and large Stokes shifts as well as the special electronic structure of the rare earth ions. …”
Section: Introductionmentioning
confidence: 99%